Träffpunkten : En plats att stråla samman - Johansson,Christine; Johansson,Katja (2005)
This essay focuses on a träffpunkts-activity within LSS's disability care, which started a year ago. The study has an evaluating perspective. The purpose of this essay is to describe the activity, study its intentions and to describe how far it has come reaching its intentions/goals. The questions we have focused on are: What were Träffpunkten's goals and how far has it evolved during the past year. Further more we have examined what kind of social interaction developing between guests and LSS-activity users and how much the activity's intentions show in it today. We used a qualitative method in this essay. To get answers to our questions, we have interviewed persons involved in Träffpunkten and others at Vård och Omsorgsförvaltningen. We have also observed interaction at Träffpunkten and compiled a poll that we have sent to LSS-activity users. Analyzes of the respondent's answers to our questions shows that Träffpunkten has started reaching its goals and has an ongoing integration process.
Keywords: personer med funktionshinder; personer med funktionshinder -delaktighet i samhället; socialt arbete; Care and help to handicapped; Handikappade, vård och rehabilitering